From neglect to spotlight: the underappreciated role of B cells in cutaneous inflammatory diseases - Lee, Eun-Gang; Oh, Ji Eun (Frontiers in Immunology, 2024)
The skin, covering our entire body as its largest organ, manifests enormous complexities and a profound interplay of systemic and local responses. In this heterogeneous domain, B cells were considered strangers. Yet, recent studies have highlighted their existence in the skin and their distinct role in modulating cutaneous immunity across various immune contexts. Accumulating evidence is progressively shedding light on the significance of B cells in maintaining skin health and in skin disorders. Herein, we integrate current insights on the systemic and local contributions of B cells in three prevalent inflammatory skin conditions: Pemphigus Vulgaris (PV), Systemic Lupus Erythematosus (SLE), and Atopic Dermatitis (AD), underscoring the previously underappreciated importance of B cells within skin immunity. Moreover, we address the potential adverse effects of current treatments used for skin diseases, emphasizing their unintentional consequences on B cells. These comprehensive approaches may pave the way for innovative therapeutic strategies that effectively address the intricate nature of skin disorders.